2015
DOI: 10.1038/srep14996
|View full text |Cite
|
Sign up to set email alerts
|

Signature of a polyamorphic transition in the THz spectrum of vitreous GeO2

Abstract: The THz spectrum of density fluctuations, S(Q, ω), of vitreous GeO2 at ambient temperature was measured by inelastic x-ray scattering from ambient pressure up to pressures well beyond that of the known α-quartz to rutile polyamorphic (PA) transition. We observe significant differences in the spectral shape measured below and above the PA transition, in particular, in the 30–80 meV range. Guided by first-principle lattice dynamics calculations, we interpret the changes in the phonon dispersion as the evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The structure of amorphous and crystalline GeO 2 at high pressure is of interest due to its use in technical glasses and due to fundamental questions related to the compaction mechanism on the atomic scale in this archetypal network forming system [1][2][3][4][5][6][7][8][9][10][11][12][13]. The compaction mechanism in the amorphous phase has important geophysical and geochemical implications, as GeO 2 is a structural analog of SiO 2 , the main component in silicate melts present in Earth's mantle.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of amorphous and crystalline GeO 2 at high pressure is of interest due to its use in technical glasses and due to fundamental questions related to the compaction mechanism on the atomic scale in this archetypal network forming system [1][2][3][4][5][6][7][8][9][10][11][12][13]. The compaction mechanism in the amorphous phase has important geophysical and geochemical implications, as GeO 2 is a structural analog of SiO 2 , the main component in silicate melts present in Earth's mantle.…”
Section: Introductionmentioning
confidence: 99%
“…Based on DFT calculations, the change was interpreted as the abrupt evolution from a quartz-like to a rutile-like behavior of amorphous GeO 2 , and indicated that the collective dynamics of amorphous GeO 2 inthe THz range was strongly sensitive to the changes in the local structure. The investigations of the THz dynamics provide an important insight into the polyamorphic transition and link it to the transformations of elastic properties(Cunsolo et al 2015).…”
mentioning
confidence: 99%
“…To understand these 85 unusual experimental results we carried out MD calculations on vitreous GeO 2 and did not find any high pressure region in which Ge-O showed a purely pentahedrally coordinated state (Figure 10) 86 . Subsequent to our studies 86 their have been several theoretical and experimental studies like EXAFS, inelastic X-ray scattering, and neutron diffraction, but none of them supported the presence of a pure pentahedral state of Ge-O thus vetting our results [87][88][89][90][91][92] . Since collection of good data of vitreous samples is experimentally challenging, and analysis of this data is non-trivial, specially if it is noisy, it is possible that the extracted coordination of Ge-O from earlier X-ray and neutron diffraction data may not have been reliable 85 .…”
Section: Germanium Dioxidementioning
confidence: 83%